Gay and Lesbian Historical Fiction - Jones, N. author. aut Link
XII, 218 p.
Keywords: The first extensive study of gay and lesbian historical fiction, this book demonstrates how the highly popular sub-genre helps us understand gay and lesbian history. It shows not only why the sub-genre should be taken more seriously by historians but also how it implicitly works to ameliorate divisions between Christianity and homosexuality.